Enhancing Educational Quality Through Effective Communication in Private Universities - M Mahbubi; Abd. Hamid Cholili; Ali Anhar Syi’bul Huda; Shuhada (CV. Gerasi Insan Nusantara, 2025)
This study examines the role of communication among stakeholders in enhancing the quality of education at private universities (PTS) in Probolinggo. By analyzing the interactions between university leadership, faculty, students, alumni, and local government, this research explores how effective communication fosters collaboration and institutional development. A qualitative approach is employed through interviews, observations, and literature analysis to identify key factors contributing to educational quality improvement. Findings indicate that effective communication enhances student performance, institutional reputation, and graduate employability. For instance, the implementation of regular academic forums and open dialogues between university leadership and faculty has facilitated curriculum alignment with industry needs, improving the relevance of education. Additionally, alumni engagement through mentoring programs and partnerships with businesses has expanded career opportunities for graduates, demonstrating the impact of communication in building professional networks. The study also clarifies that